A framework for discretionary effort based on performance expectancies in integrated work environment - Katoma, Victor (Graduate School of Business (GSB), 2019)
In an age of immense business competition, and far-reaching leadership requirements, Discretionary Effort is required as part of a value creation and enhanced performance strategy. Discretionary Effort is the unsolicited effort, which employees expend when certain work expectations are met. Traditionally, Expectancy, Valence and Instrumentality (VIE) have been the leading variables of this construct. Research has however, revealed that self-affirmation (A) adds another important dimension to the Discretionary Effort Framework (VIEA) (April & Katoma, 2008). This research investigated Discretionary Effort (the full VIEA) in an integrated work environment, using professional networks, consisting primarily of 1548 managers and specialists, who were either co-located or virtually located in different sectors. The survey instrument was divided into four parts, with the first and second parts measuring expectancies at individual and work level respectively. The third and fourth parts measured the degree of discretionary behavior of employees, and the extent to which organizations considered these relevant. The data were collected through faxes, emails, and online survey tools from employees attending leadership courses at the Business School. Results revealed that Discretionary Effort was not significantly different in clusters at the micro level of units of employees, but significantly different at the macro (sector) level - with service-oriented sectors, such as retail, scoring higher Discretionary Effort compared to product-oriented industries, such as engineering. Within the clusters or units, process-oriented influencer variables, such as experience, showed significant effects on the aforementioned Discretionary variables. Employees were also more generally concerned with higher levels of needs (social needs), as specified in Maslow's hierarchy of needs (Maslow, 1968), partly due to interpersonal interrelations and knowledge-dependent professional networks. The most significant hypotheses included individual network learning, team sustainability, effort learning all at p<.001, while interpersonal performance and mutual reciprocity were at p<.10. Construct validity, using covariates, revealed an acceptable Discretionary Effort model fit of VIEA: χ = 102, df = 17, RMSEA = .0584, NFI = .95, CFI = .95 and GFI = .983.